Efficacy of Herbicide Combinations and Seeding Rates on Growth and Yield of Bread Wheat and its Associated Weeds - Jalal Saleh Jalal; Krmanj Yousif Naby (Zanco Journal of Pure and Applied Sciences, 2023)
herbicides have the considerable influence on weed control especially when combined with other herbicides and different seeding rates as an integrated weed management in wheat fields. This study was carried out to evaluate the effects of two herbicides with different concentrations as combinations. First, Atlantis 240 gm. ha-1 + Granstar 35 gm. ha-1 (low dose) second Atlantis 320 gm. ha-1 + Granstar 50 gm. ha-1 (recommended dose) third Atlantis 400gm. ha-1 + Granstar 65 gm. ha-1 (higher dose) comparing with weedy check and weedy free plots as a control treatments, and different seeding rates (75, 100, 125 kg. ha-1) on bread wheat at two different locations (Grdarasha and Ainkawa) and were distributed with three replicates using the randomized complete block design (RCBD). The results indicated that wheat grain yield had the highest value was 8.9 ton. ha-1 by low dose of Atlantis. 240 gm. ha-1 + Granstar. 35 gm. ha-1 at Grdarasha where at Ainkawa was 6.29 ton. ha-1 by high dose of Atlantis. 400 gm. ha-1 + Granstar. 65 gm. ha-1 herbicides. In addition, seeding rates had significant impacts on wheat grain yield, which it was achieved highest grain yield at higher seeding rates at both locations. Whereas, herbicide combinations of higher dose of Atlantis. 400 gm. ha-1 + Granstar. 65 gm. ha-1 reduced total weed number and weight significantly to the lowest value at both locations. As well as highest seeding rates of bread wheat had minimum total weed number and weight at both locations. Herbicide combinations with higher seed rate of economic crops together can control weeds more efficiently in wheat fields.